Risk management, regulatory frameworks and contributory pension scheme sustainability in Nigeria - Aliu, Olanrewaju Atanda (2019)
Empirical evidence has shown that occupational pension schemes have continued to face crises that necessitate pension reforms with concern on sustainability among the focal points. Consequently, there have been waves of occupational pension reforms globally. Previous studies show mixed evidence with respect to the propensity of the reforms towards achieving a sustainable occupational pension scheme. Drawing mainly from institutional theory, this study examines the impact of risk management in moderating the effects of regulatory frameworks (investment strategy, corporate governance, transparency, and compliance) on contributory pension scheme sustainability in Nigeria. Mixed method design was adopted with survey of 212 and interviews of nine managers of contributory pension scheme operators respectively. The survey results show there is evidence of positive significant level of contributory pension scheme sustainability in Nigerian. It was found that investment strategy, corporate governance, and transparency have significant positive direct effects on contributory pension scheme sustainability while compliance does not. Also, risk management has a significant negative moderating effect on the relationship between investment strategy and contributory pension scheme sustainability, while the moderating effect of risk management on the relationship between transparency and contributory pension scheme sustainability is significantly positive. Contrarily, risk management fail to show moderating effects on corporate governance and compliance. The interview results reveal that investment strategy promotes diversification and risk reduction, while corporate governance serves as a protection of contributory pension scheme fund. The results further reveal that transparency facilitates information access while compliance serves as adherence and deterrence factor among others. The implications of the study were presented for policy formulation towards improving the sustainability of Nigerian contributory pension scheme.